Tingkat Preferensi Pedestrian dan Walkability Koridor Jalan di Kota Tua Jakarta - Pizza Agradiana (Prodi Arsitektur Universitas Matana, 2020)
Walkability is being a way to assess the environmental quality of walking activities. This study discusses the level of walkability in 6 main road corridors in the Kota Tua Jakarta area using scoring assessment methods on four aspects of the observed Walkability Level namely the level of security and safety, comfort level, the availability factor of pedestrian support facilities, and the quality factor or physical condition of pedestrian facilities the feet. From the results of the assessment, it is linked to the pedestrian preferences in choosing the walking route from the transit mode of transportation (train station and busway stop). With the location of the study on several road corridors in the Kota Tua Jakarta region, Jl. Pintu Besar Utara, Jl. Stasiun Kota, Jl. Lada, Jl. Jembatan Batu, Jl. Great South Door and Jl. Asemka. The results found that the level of walkability of a road does not always affect the user's walking preferences. Although the level of Walkability is high, it is not necessarily a pedestrian preference in the walking route.